(Strept)avidin as Host for Biotinylated Coordination Complexes: Stability, Chiral Discrimination, and Cooperativity - Loosli, Andreas; Rusbandi, Untung Edy; Gradinaru, Julieta; Bernauer, Klaus; Schlaepfer, Carl Wilhelm; Meyer, Michel; Mazurek, Sylwester; Novic, Marjana; Ward, Thomas R. (My University, 2006)
To determine the stepwise association constants, to assess cooperativity and chiral discrimination properties of (strept)avidin toward biotinylated coordination complexes, diastereopure [Ru(bpy)2(Biot-bpy)]2+ (1) complexes were synthesized. Analysis of the CD titration data suggests a strong cooperativity between the first and the second binding events in tetrameric (strept)avidin and a pronounced difference in affinity between avidin and streptavidin for the dicationic guest 1 as well as modest enantiodiscrimination properties with avidin as host.